Clinical Experience with Treatment of Angioleiomyoma - Kyoung Sik Woo; Sang Hun Kim; Han Seong Kim; Pil Dong Cho (Archives of Plastic Surgery, 2014)
Background Angioleiomyoma, a vascular leiomyoma, is a rare, benign smooth-muscle tumor that originates in the tunica media of vessels. It occurs anywhere in the body, most frequently in the lower extremities. Methods We reviewed the medical records of 16 patients who were treated for angioleiomyoma between 2000 and 2012. The clinical features of angioleiomyoma and the correlation between symptoms and pathological subtypes were investigated. Results There were 9 males and 6 females. Ages of the patients ranged from 21 to 61. Pain was the primary symptom in 44% of the patients. Tumors were smaller than 2.0 cm in all dimensions and were located in the face in 4 patients, whereas 5 lesions occurred in the upper extremities and the remaining 7 in the lower extremities. Three histologic subtypes were identified: solid, venous, and cavernous. The subtypes did not correlate with the clinical symptoms. Conclusions Angioleiomyoma appears to be a rare tumor that occurs in the face and the extremities. The tumor usually occurs in middle age. A differential diagnosis of this tumor is difficult, but the tumor should be considered in the diagnosis of painful subcutaneous masses. Ultrasonography and magnetic resonance imaging can be helpful in the diagnosis of angioleiomyoma. These tumors can be successfully treated with simple excision, with a low recurrence rate.